2018
DOI: 10.1002/open.201800185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 3‐Bromo‐4,5‐dihydroisoxazole Derivatives on Nrf2 Activation and Heme Oxygenase‐1 Expression

Abstract: Natural and synthetic electrophilic compounds have been shown to activate the antioxidant protective Nrf2 (nuclear factor erythroid 2‐related factor 2)/heme oxygenase‐1 (HO‐1) axis in cells and tissues. Here, we tested the ability of different isoxazoline‐based electrophiles to up‐regulate Nrf2/HO‐1. The potency of activation is dependent on the leaving group at the 3‐position of the isoxazoline nucleus, and an additional ring on the molecule limits the Nrf2/HO‐1 activating properties. Among the synthetized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Recently, the 3-Bromo-Δ 2 -isoxazoline nucleus has gained attention as an emerging electrophilic scaffold, which was successfully used in the design of covalent inhibitors of different classes of Cys-containing enzymes. [213][214][215][216][217][218][219][220][221][222][223][224] Moreover, the comparison of the proteome targets of Chloro and Bromo-isoxazoline revealed that the first achieve weaker labelling with the same targets compared to the bromide counterparts. 225 3-Bromo-Δ 2 -isoxazoline represents an ideal warhead with a relatively low reactivity towards nucleophiles unless orientated at a distance and angle favorable for the reaction.…”
Section: -Bromo Isoxazolinesmentioning
confidence: 99%
“…Recently, the 3-Bromo-Δ 2 -isoxazoline nucleus has gained attention as an emerging electrophilic scaffold, which was successfully used in the design of covalent inhibitors of different classes of Cys-containing enzymes. [213][214][215][216][217][218][219][220][221][222][223][224] Moreover, the comparison of the proteome targets of Chloro and Bromo-isoxazoline revealed that the first achieve weaker labelling with the same targets compared to the bromide counterparts. 225 3-Bromo-Δ 2 -isoxazoline represents an ideal warhead with a relatively low reactivity towards nucleophiles unless orientated at a distance and angle favorable for the reaction.…”
Section: -Bromo Isoxazolinesmentioning
confidence: 99%
“…240−243 Such compounds have been subject to early reactivity/promiscuity analyses 244 which showed that the reaction proceeds through an addition−elimination mechanism, displacing the halogen at the electrophilic 3-position, which has been hypothesized to be favored in protease-like enzymes by stabilization of the tetrahedral intermediate via the oxyanion hole. 245 With respect to human target proteins, Pinto et al 246 recently showed by MS and X-ray crystallography (PDB code: 6FFM) that the BDHI 125 (Figure 39A) covalently binds to Cys151 of the KEAP1 protein, allowing the modulation of the antioxidant system NRF2/HO-1. The Conti group 247 described spirocyclic BDHIs like 126 (Figure 39A) targeting the catalytic Cys152 in human glycerinaldehyde-3-phosphate-dehydrogenase (GAPDH).…”
Section: Cysteine Targeting By Reversible S N Ar Reactionsmentioning
confidence: 99%
“…3-Halo-4,5-dihydroisoxazoles (3-halo­isooxazolines) such as the natural product acivicin ( 123 ) and its more active synthetic 3-bromo-4,5-dihydro­isoxazole (BDHI) derivative 124 (Figure A) are well known for their ability to covalently inhibit cysteine-dependent enzymes like human trans­glutaminase 2 and for their activity on parasitic enzymes. Such compounds have been subject to early reactivity/​promiscuity analyses which showed that the reaction proceeds through an addition–elimination mechanism, displacing the halogen at the electrophilic 3-position, which has been hypothesized to be favored in protease-like enzymes by stabilization of the tetrahedral intermediate via the oxyanion hole . With respect to human target proteins, Pinto et al recently showed by MS and X-ray crystallography (PDB code: 6FFM) that the BDHI 125 (Figure A) covalently binds to Cys151 of the KEAP1 protein, allowing the modulation of the antioxidant system NRF2/HO-1. The Conti group described spiro­cyclic BDHIs like 126 (Figure A) targeting the catalytic Cys152 in human glycerin­aldehyde-3-phosphate-dehydrogenase (GAPDH).…”
Section: Targeting the Cysteine Side Chainmentioning
confidence: 99%
See 1 more Smart Citation
“…For the same reason, the 3‐bromo derivatives are much more represented and interesting for medicinal chemistry research, being the 3‐bromo‐4,5‐dihydroisoxazole scaffold an appealing warhead for the covalent inhibition of target enzymes and a polyvalent synthetic intermediate. Indeed, over the years, this warhead has been exploited in several covalent‐acting biologically active compounds, [10–12] including antibiotic, [13] antiparasitic, [14–21] and neuroprotective agents [22–24] . Concerning the mechanism of action, the 3‐bromo‐4,5‐dihydroisoxazole can react at the C3 position with nucleophilic amino acidic residues of a catalytic triad, e. g., cysteine, threonine, and serine, through an addition‐elimination mechanism (Ad−E), represented in Scheme 1, which may lead to the formation of a covalent bond and inactivation of the target (e. g., GAPDH, cathepsin L‐like cysteine proteases) [9] .…”
Section: Introductionmentioning
confidence: 99%